New circuit configuration and control strategy of modular multilevel converter for large scale photovoltaic systems / Ahmed Ibrahim Ibrahim Abbas Ahmed Elsanabary - Ahmed Ibrahim , Ibrahim Abbas Ahmed Elsanabary (2022)
Photovoltaic (PV) energy markets have been widely spread and are becoming one of the leading energy generation capacities globally. The development of grid-connected PV systems is the main target as it exceeds 99 % of the PV installed capacity due to the comparatively low cost and less maintenance compared to stand-alone systems. Nevertheless, the traditional large-scale PV inverters suffer from power loss of the central maximum power point tracking (MPPT) system, the lack of modularity, the low voltage ratings, and limitation of the switch power ratings because of the use of central PV inverters. Modular medium-voltage multilevel converters are very promising to solve the problems of large-scale PV systems. However, the integration of multilevel converters into large-scale PV systems suffers from unbalanced power generation during partial PV shading conditions. This problem is fully addressed in the thesis, and a distinctive structure of the modular multilevel converter (MMC) for grid-connected PV plant is proposed. The proposed PV-MMC system provides direct connection of the PV arrays to the converter submodules, scalability, independent MPPT, enhanced power quality, and internal power flow capabilities. An energy balancing strategy to control the power flow inside the PV-MMC converter is proposed. It controls the internally generated leg current to balance the power flow inside the converter and inject a three-phase balanced current into the grid. Afterward, a new circuit configuration of the PV-MMC system is proposed to enhance the balancing capability of MMC under severe power unbalance conditions. This circuit connects the upper and lower SMs of the MMC in parallel to the same PV arrays through isolated dc-dc converters. Moreover, a modified control structure is designed to control the proposed system, which is less complex and yet very effective compared to the other control structures. It deals only with the leg power unbalance conditions and inject dc leg current into the phases to balance the power flow of the converter. Simulation and Hardware-in-the-loop tests are performed to demonstrate the performance of the proposed grid-connected PV-MMC systems. The obtained results show the capability of the proposed systems to rebalance the power transfer inside the converter and inject a three-phase balanced set of grid currents. In addition, excellent dynamic performance of controllers, low measured harmonics (below 5 %), and low SM voltage ripple (3.98%) are obtained. The objective of the thesis is achieved by investigating the MMC for the application to grid connected large-scale PV systems. The related analysis and comparisons show the capability and power quality of the proposed PV-MMC systems. The proposed energy balancing strategy can eliminate the PV power unbalance and work under different conditions of solar irradiances. Moreover, the proposed circuit configuration provides extended balancing capability of the MMC up to extreme conditions.